Nuclear phase transitions near the critical points: a study with the Relativistic Hartree-Bogoliubov model, the Interacting Boson Model and the Boson Coherent-State Framework - Fossion, R. (HNPS Advances in Nuclear Physics, 2020)
We present an analysis of the intensity of 2-particle transfer reactions in the Interacting Boson Model (IBM), and in the Boson Coherent-State framework, as a tool to study nuclear phase transitions. We study transfer reactions between two ground states, and between the ground state and the band head of the beta-vibrational band. We suggest characteristic fingerprints that should allow experimentalists to identify the critical points of the nuclear phase transition. Two analytical solutions, X(5) and E(5), have been proposed recently for two of the critical points. We present a study within the Relativistic Hartree-Bogoliubov model (RHB), using Potential-Energy Surfaces (PES), to test whether the initial approximations made in deriving the analytical solutions are valid.